INFLUENCE SOCIAL MEDIA MARKETING ACTIVITIES AGAINST BRAND LOYALTY DIRECTLY OR THROUGH CONSUMER SATISFACTION AND BRAND EQUITY ON THE LARGEST E-COMMERCE IN INDONESIA - Daya, Mardiana; Siagian, Yolanda Masnita; Kurniawati, Kurniawati (Universitas Brawijaya, Indonesia, 2022)
Social Media Marketing is all strategic formations in sales communication carried out through social media. Social Media Marketing is considered more effective than traditional marketing communications such as print or electronic media, so Social media marketing is considered to be able to increase brand loyalty which has an impact on customers who will consistently use the product repeatedly, will inform, and even recommend the product to others. This study analyzes the influence of Social Media Marketing on Brand Loyalty directly and its effect through the mediation of consumer satisfaction & Brand equity on Brand Loyalty. The sample was taken from 195 followers of the Instagram account of the largest e-commerce platform in Indonesia, including Tokopedia, Shopee, Lazada, Bukalapak, OLX, and others. The research uses quantitative methods with an explanatory research approach, while hypothesis testing is carried out with SEM (Structural Equation Model) analysts. The research shows that social media marketing has a direct and significant effect on brand equity and consumer satisfaction, but social media marketing has no effect on brand loyalty. Brand equity has a direct and significant effect on brand loyalty, but consumer satisfaction has no effect on brand loyalty. From this research, it was found that it is so important to optimize the use of social media marketing to reach a wider scope. Attractive social media marketing can influence consumer perceptions to form a good impression of a brand. Previous research stated that an increase in social media activity and brand equity affects consumers’ desire to buy products, an increase in brand equity will also impact high brand loyalty. However, it needs to be re-examined to find out the addition of the right variable as mediation to see the influence between customer satisfaction on brand loyalty and social media marketing on brand loyalty.